No student left behind: A didactic proposal for teaching English using ZPD - Rivera-Galdos, Karla Lucía (My University, 2023)
This proposal aims to interpret Vygotsky’s Zone of Proximal Development (ZPD) for teaching English in a heterogenous class. The Simple Past tense will be taught to 5TH-grade elementary school kids who have different levels of prior knowledge on the subject but share the same class. Using ZPD, mediation, scaffolding, and the assistance of the more able peer, we will get all the students to develop their cognitive functions to the same extent. Learners will benefit from social interaction to interiorize knowledge and work following ZPD: first with assistance to get to the point of working with autonomy. There is some work around ZPD in the language classroom but there is not much evidence on how this could develop learning in heterogeneous classes. This proposal will show how we can bridge the gap of ZPD using collaborative work, negotiation, and critical thinking to enhance learning.
Keywords: ZPD; Vygotsky; learning; scaffolding; interaction; Máster Universitario en Enseñanza de Inglés como Lengua Extranjera